Clinical translation of a mesenchymal stromal cell‐based therapy developed in a large animal model and two case studies of the treatment of atrophic pseudoarthrosis. (1st June 2017) - Prat, Salvi; Gallardo‐Villares, Santiago; Vives, Marian; Carreño, Ana; Caminal, Marta; Oliver‐Vila, Irene; Chaverri, Daniel; Blanco, Margarita; Codinach, Margarita; Huguet, Pere; Ramírez, José; Pinto, Javier A.; et al.
Abstract: Pseudoarthrosis is a relatively frequent complication of fractures, in which the lack of mechanical stability and biological stimuli results in the failure of bone union, most frequently in humerus and tibia. Treatment of recalcitrant pseudoarthrosis relies on the achievement of satisfactory mechanical stability combined with adequate local biology. Herein we present two cases of atrophic pseudoarthrosis that received a tissue‐engineering product (TEP) composed of autologous bone marrow‐derived mesenchymal stromal cells (BM‐MSC) combined with deantigenized trabecular bone particles from a tissue bank. The feasibility of the treatment and osteogenic potential of the cell‐based medicine was first demonstrated in an ovine model of critical size segmental tibial defect. Clinical‐grade autologous BM‐MSC were produced following a good manufacturing practice‐compliant bioprocess. Results were successful in one case, with pseudoarthrosis resolution, and inconclusive in the other one. The first patient presented atrophic pseudoarthrosis of the humeral diaphysis and was treated with osteosynthesis and TEP resulting in satisfactory consolidation at month 6. The second case presented a recalcitrant pseudoarthrosis of the proximal tibia and the Masquelet technique was followed before filling the defect with the TEP. This patient presented a neuropathic pain syndrome unrelated to the treatment that forced the amputation of the extremity 3 months later. In this case, the histological analysis of the tissue formed at the defect site provided evidence of neovascularization but no overt bone remodelling activity. It is concluded that the use of expanded autologous BM‐MSC to treat pseudoarthrosis was demonstrated to be feasible and safe, provided that no clinical complications were reported, and early signs of effectiveness were observed. Copyright © 2016 John Wiley & Sons, Ltd.